The rule of empires those who built them, those who endured them, and why they always fall - Parsons, Timothy 1962- (Oxford University Press, 2015)
In this text, Timothy Parsons gives a sweeping account of the evolution of empire from its origins in ancient Rome to its most recent 20th-century embodiment. He explains what constitutes an empire and offers suggestions about what empires of the past can tell us about our own historical moment.